If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2y + 12 = 66 Reorder the terms: 12 + 2y = 66 Solving 12 + 2y = 66 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + 2y = 66 + -12 Combine like terms: 12 + -12 = 0 0 + 2y = 66 + -12 2y = 66 + -12 Combine like terms: 66 + -12 = 54 2y = 54 Divide each side by '2'. y = 27 Simplifying y = 27
| z^2+14z=-45 | | X*240=12 | | 6=35 | | -6x-3(-3x+17)=-36 | | (5s+6)(s-2)= | | -7(4-4x)=-168 | | 8(t-2)+6t=7(2t+3)-9 | | -6(-7x-1)-x=-158 | | 7n-15=-16+8n | | -4x-6(-2x+15)=-10 | | 1/2(4/3)(3.14)(2.5)^3 | | -2x-3=2x+9 | | 4(6n-7)=140 | | 3(x-1)=7+5 | | n^2+9=34 | | Y=29(3)x | | 4(6n-7)=40 | | Y=29(3) | | 2/3x12/11 | | (n-6)(n-4)= | | 2j-12=2 | | -5.7=1.9+1.9z | | 4n-3=29+8n | | 2x-52=88 | | 8x-11+15x+3x+9=180 | | -5x-4(-x-17)=76 | | y+7=7(x-2) | | -10(b+645)=-490 | | 15-1/2b= | | 4w-60=440 | | 2g-17=1 | | y-6=6(x+6) |